The Effect Of The Application Of The Problem-Based Learning Model On Improving Students' Learning Outcomes In The Learning Of Fiqih In Grade Viii Mts Al-Baitul Qadim Airmata - Siti Ida Yanti; Siti Asiyah; Asia Sengaji (EDUJAVARE: International Journal of Educational Research, 2026)
The primary issue addressed in this study is the low level of student learning outcomes in the *Fiqh* (Islamic jurisprudence) subject, specifically regarding the topic of regulations concerning halal and haram foods. This issue stems from the dominance of the lecture method, which tends to render students passive, limits their participation in discussions, and hinders their ability to relate the subject matter to real-life situations. To address this, the study aims to examine the implementation of the Problem-Based Learning (PBL) model in *Fiqh* instruction and to assess its impact on improving the learning outcomes of eighth-grade students at MTs Al-Baitul Qadim Airmata. A quantitative approach was employed, utilizing a pre-experimental research type with a one-group pretest-posttest design. The study sample consisted of 14 students, selected using the saturated sampling technique. Data collection instruments included pretests and posttests, interviews, and documentation, while data analysis involved normality testing and hypothesis testing using a paired-sample t-test. The results indicate a significant improvement in learning outcomes, with the average pretest score rising from 38.85 to 92.00 on the posttest. The t-test yielded a significance value of 0.001 (p < 0.05), confirming that the implementation of PBL had a significant impact on learning outcomes. The study demonstrates that the PBL model is effective in enhancing conceptual understanding, active participation, and student engagement in *Fiqh* lessons, thereby offering a relevant alternative teaching strategy for educators to improve the quality of education in *madrasas*.